Micromachined Double‐Membrane Mechanically Tunable Metamaterial for Thermal Infrared Filtering - Oleg Bannik; Fedor Kovalev; Mingkai Liu; Michal Zawierta; Dilusha Silva; Lorenzo Faraone; Mariusz Martyniuk; Ilya Shadrivov (Advanced Photonics Research)
A mechanically tunable metamaterial concept for transmissive spectral discrimination within the long‐wavelength infrared (LWIR) range (8–12 μm) is proposed and validated. The metamaterial consists of a periodically perforated gold membrane that exhibits the extraordinary optical transmission (EOT) effect, combined with a parallel silicon membrane separated by an air gap. This structure acts as a band‐pass filter, with its spectral position highly sensitive to the separation gap between the membranes, which influences the resonance conditions for EOT. Numerical simulations predict tunability across the entire LWIR range with a membrane displacement of just 0.5 μm. This concept is experimentally demonstrated through vertical electrostatic actuation of the silicon membrane relative to the gold layer facilitated by a micro‐electromechanical systems (MEMS) approach. The measured optical transmission of the fabricated MEMS‐enabled, spectrally tunable plasmonic metamaterial shows good agreement with the numerically modeled spectral filter characteristics. Further refinement of this method could pave the way for a variety of low‐cost, low‐power miniature devices, enhancing spectroscopy and multispectral imaging capabilities in the thermal infrared range.